Binary Mixtures of Imidazolium-Based Protic Ionic Liquids. Extended Temperature Range of the Liquid State Keeping High Ionic Conductivities - Abdurrokhman, Iqbaal; Martinelli, Anna (Frontiers in Chemistry, 2022)
Binary mixtures based on the two protic ionic liquids 1-ethylimidazolium triflate ([C2HIm][TfO]) and 1-ethylimidazolium bis(trifluoromethanesulfonyl)imide ([C2HIm][TFSI]) have been investigated, with focus on phase behavior, ionic conductivity, and intermolecular interactions as a function of composition (χTFSI indicating the mole fraction of the added compound). It is found that on addition of [C2HIm][TFSI] to [C2HIm][TfO], the melting temperature is first decreased (0 <χ≤ 0.3) and then suppressed (0.3 <χ≤ 0.8) resulting in mixtures with no phase transitions. These mixtures display a wide temperature range of the liquid state and should be interesting for use in devices operating at extreme temperatures. The ionic conductivity does not vary significantly across the composition range analyzed, as evidenced in the comparative Arrhenius plot. The activation energy, Ea, estimated by fitting with the Arrhenius relation in a limited temperature range (between 60 and 140 °C) varies marginally and keeps values between 0.17 and 0.21 eV. These marginal differences can be rationalized by the initially very similar values of the two neat protic ionic liquids. Vibrational spectroscopy, including both Raman and infrared spectroscopies, reveals weakening of the cation–anion interactions for increasing content of [C2HIm][TFSI], which is reflected by the blue shift of the average N-H stretching mode and the red shift of the S-O stretching mode in the TfO anion. These trends correlate with the higher disorder in the mixtures observed by DSC and are evidenced by the decrease and suppression of the melting temperature as the amount of [C2HIm][TFSI] is increased.